PENGUATAN NILAI MORAL DALAM IMPLEMENTASI ARTIFICIAL INTELLIGENCE TERHADAP GENERASI Z DI LINGKUNGAN STASI ST. ANTONIUS PADUA MELALUI PENDAMPINGAN IMAN - Gerardus Bernardus Duka; Valentinus Kopong Masan; Bonefantura Jemy Bria (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The development of Artificial Intelligence (AI) has brought significant changes in the learning, communication, and identity-building patterns of Generation Z. On the one hand, AI provides easy access to information and digital creativity; on the other hand, unsupervised use has the potential to create a value crisis, such as low moral responsibility, misuse of technology, and degradation of digital ethics. This situation is also felt by young people in the St. Antonius Padua Station environment who live in the flow of massive digitalization. This Community Service Program aims to strengthen the moral values of Generation Z in the implementation of AI through a structured and contextual faith mentoring model. The methods used include AI literacy socialization, mentoring based on faith reflection, digital ethics case discussions, and participatory evaluation. This approach integrates Christian moral teachings with the principles of responsibility, wisdom, and honesty in the use of technology. The results show a significant improvement in the participants' ethical understanding and moral awareness. Quantitatively, the average moral value score increased from 31.75 before the intervention to 79.00 after the intervention (a 47.25-point increase). This achievement exceeded the predetermined success indicators, with ≥75% of participants experiencing a minimum 20% increase in AI literacy scores, and ≥70% of participants correctly identifying forms of AI misuse in case studies. The program also successfully established a digital faith mentoring group with more than 10 members as a form of sustainability. This program emphasizes that faith mentoring is a relevant pastoral strategy in shaping digital character that is rooted in Evangelical values and responsive to the challenges of the times.